2017
DOI: 10.1089/gtmb.2016.0240
|View full text |Cite
|
Sign up to set email alerts
|

Influences ofIL-1b-3953 C>T andMMP-9-1562C >TGene Variants on Myocardial Infarction Susceptibility in a Subset of the Iranian Population

Abstract: The findings suggest that the minor alleles of the two polymorphisms under study both have protective effects with respect to MI susceptibility in the Iranian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…[ 15 – 23 ] Table 2 summarizes the main features of each study. Two studies were based on Asian populations, [ 16 , 19 ] while the other studies were based on Caucasian populations. [ 15 , 17 , 18 , 20 23 ] The results of the HWE tests for genotypic distribution in controls are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 15 – 23 ] Table 2 summarizes the main features of each study. Two studies were based on Asian populations, [ 16 , 19 ] while the other studies were based on Caucasian populations. [ 15 , 17 , 18 , 20 23 ] The results of the HWE tests for genotypic distribution in controls are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have revealed that IL-1β + 3954C/T is related to an increased risk of MI in Caucasian populations. [ 15 , 17 ] However, Daraei et al [ 19 ] demonstrated that the TT genotype of the IL-1β + 3954C/T polymorphism was associated with a significant MI-protective effect in an Asian population, and Wang et al [ 16 ] showed that IL-1β + 3954C/T was not correlated with MI risk in a Chinese population. MI is a multifactorial disease and polymorphisms may also have different effects on populations as a result of diverse environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is the active enzyme in MMP family with the largest molecule size of all members. It mediates the formation, development, and rupture of atherosclerotic plaques by mediating metastasis, viability, apoptosis, and extracellular matrix remodeling of vascular smooth muscle cells [ 21 , 22 ]. Studies have found that elevated levels of MMPs are closely associated with the development of unstable angina and AMI [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Анализ рецессивной генетической модели (ТТ vs. ТС+СС) выявил, что лиц с ТТ-генотипом было больше в группе контроля (здоровые лица), чем в группе пациентов ИМ (14,2% против 6%, р=0,04). Логистический регрессионный анализ с поправкой на возраст, пол, уровень триглицеридов (ТГ), общего холестерина (ОХ), липопротеинов высокой плотности (ЛПВП), липопротеинов низкой плотности (ЛПНП), артериального давления (АД), сахарный диабет (СД), ИМТ и курение показал протективный эффект в отношении ИМ в гомозиготной генетической модели ТТ-генотипа (ТТ против СС; ОR=0,18, 95% ДИ: 0,04-0,72; р=0,01) и в рецессивной генетической модели (ТТ против ТС+СС, до корректировки ОR=0,39; 95% ДИ: 0,15-0,96; р=0,04 и после корректировки; ОR=0,15; 95% ДИ: 0,04-0,58; р=0,006) [19].…”
Section: Review Interleukin-1в Gene Rs1143634 Polymorphism and Cardio...unclassified